Fern Species-Area Relationship in Urban Anthropogenic Islands in Slawi, Tegal, Central Java - Sedayu, Agung; Putri, Novita; Aminudin, Aminudin; Mawardi, Muchtar; Noer, M. Isnin; Maulana, Lana (Journal of Tropical Biodiversity and Biotechnology, 2024)
In anthropogenic islands as urban parks, the fern species richness and composition may be determined ecologically by the quality of habitat, including area greenness, or biogeographically by area size. As the development of the theory of island biogeography also includes man-made parks, it is feasible to test whether area-species relationship applies in these urban parks, and is more pronouncedly evident compared to another ecological factor, such as NDVI. Total species number and composition of 8 urban parks in a kecamatan in Tegal Regency were collected and arranged in clustering methods to understand the similarity between parks. The similarity analysis result is important for the management of the parks in Slawi. The species richness data is subsequently tested using Pearson correlation and regression against NDVI and area sizes. The relation between NDVI and species richness is non-significant (p=0.058), while area size and species richness is significant (p=0.003). This signifies that the urban fern species richness is determined by area as biogeographical factor, compared to NDVI as ecological factor. This result is important for the purpose of designing and managing urban parks as evidently size is important in the effort of attracting native biodiversity into urban parks and in turn enhancing the well-being of urban population.